Using Meta-analysis to test Capital Management And Company Performance - Deva, Rendy Nur (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this article is to determine the relationship between the influence of working capital management on Company performance.The method of writing is done by analyzing 10 previous research journals that discuss working capital management on Company performance using a meta-analysis study. the conclusions of the results this article are taken from previous research after being analyzed by meta-analysis can provide an overview that working capital management has a negative effect on Company performance